АНАЛИЗ АМИНОКИСЛОТНОГО СОСТАВА МЯСА ОВЕЦ В УСЛОВИЯХ ПАРАЗИТАРНОЙ ИНВАЗИИ - Ж. Валиева; М. Свотина; Р. Абдрахманов; З. Айтпаева; Н. Абекешев; Ж. Усенов; А. Жумабаев; Ж. Рыскалиева; А. Айткалиев (Animal Health and Biosafety, 2026)
Parasitic diseases are among the factors that may adversely affect the physiological condition and productivity of farm animals. Prolonged parasitic infections may be associated with disturbances in digestion and nutrient utilization, which are of interest when assessing the quality characteristics of livestock products. Therefore, investigation of the amino acid composition of sheep meat obtained from farms affected by parasitic diseases is of scientific and practical importance. The aim of this study was to characterize the amino acid composition of sheep meat obtained from animals kept on farms in the West Kazakhstan Region that had previously been affected by parasitic diseases. Nine muscle tissue samples were included in the study. The amino acid composition was determined by chromatographic analysis in accordance with GOST 34132–2017. The concentrations of major essential and non-essential amino acids were determined. The moisture content of the examined samples was also assessed. The amino acid profile showed marked variability among the examined samples. The highest mean values were recorded for aspartic acid, cystine, and asparagine. Among the essential amino acids, isoleucine and methionine had the highest mean concentrations. The most pronounced differences between samples were observed for cystine, asparagine, aspartic acid, isoleucine, and lysine. The moisture content ranged from 62.12% to 78.17%. The findings characterize the amino acid profile of the examined sheep meat samples and demonstrate considerable variation among samples. Given the absence of an intact control group, the observed differences cannot be unambiguously interpreted as a direct consequence of parasitic infection. They may reflect the combined effects of physiological, individual, and farm-related factors. The obtained data may provide a basis for further studies of meat quality and for assessing the relationship between the parasitic status of animals and the biochemical characteristics of muscle tissue.